The Hobbit, or, There and back again - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. (New York : Dell Rey, 1997)
Bilbo Baggins, a Hobbit who just wanted to be left alone, embarks upon a dangerous journey with thirteen dwarfs and the wizard Gandalf, eventually coming into possession of a very magical ring.
Young Adult
Keywords: Baggins, Bilbo (Fictitious character) -- Fiction; Hobbits (Fictitious characters) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Baggins, Bilbo (Fictional character) -- Fiction; Hobbits (Fictional characters) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Fantastic fiction